2020
DOI: 10.1111/deci.12429
|View full text |Cite
|
Sign up to set email alerts
|

Analytics for Cross‐Border E‐Commerce: Inventory Risk Management of an Online Fashion Retailer

Abstract: Problem statement: We present a data‐driven analytics study of a Chinese fashion retailer. The retailer fulfills cross‐border orders using online platforms, but faces inventory problems in its overseas warehouses, owing to operational complexities, such as extensive product offerings, high demand risks, and tax risks in cross‐border trade. Traditional approaches (e.g., model‐driven approaches) often fail to provide effective solutions. Therefore, this study proposes a new data‐driven approach to manage invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Van Heel et al [41] studied cross-border e-commerce export trade and found that there are obstacles in customs clearance, logistics, and supervision. Shi et al [42] conducted a data-driven analysis and research on Chinese fashion retailers and found that the risks affecting the cross-border e-commerce supply chain of enterprises include online marketing risks, cross-border e-payment risks, e-customs clearance risks, cross-border logistics risks, and credit risk. Nuruzzaman and Weber [43] have employed the qualitative research methods to identify some key issues such as supply chain facility, inventory management, and legal obstacles with today's supply chain performance of international e-commerce.…”
Section: Construction Of Risk Evaluation Index System For Cross-border E-commerce Supply Chainmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Heel et al [41] studied cross-border e-commerce export trade and found that there are obstacles in customs clearance, logistics, and supervision. Shi et al [42] conducted a data-driven analysis and research on Chinese fashion retailers and found that the risks affecting the cross-border e-commerce supply chain of enterprises include online marketing risks, cross-border e-payment risks, e-customs clearance risks, cross-border logistics risks, and credit risk. Nuruzzaman and Weber [43] have employed the qualitative research methods to identify some key issues such as supply chain facility, inventory management, and legal obstacles with today's supply chain performance of international e-commerce.…”
Section: Construction Of Risk Evaluation Index System For Cross-border E-commerce Supply Chainmentioning
confidence: 99%
“…Sometimes, the companies do not have a strong awareness of intellectual property rights and do not know much about overseas laws; infringed persons use e-commerce platforms to carry out phishing law enforcement, freeze the accounts of companies or clear their accounts, and put companies in a difficult position Cross-border transaction risk [1,5,40,[42][43][44] Credit risk C4…”
Section: Intellectual Property Disputes Risk C3mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, e-commerce characteristics are tied to online transactions and payment, so the issue of cybersecurity and privacy emerges as a significant problem (Zhong et al, 2020). With consumers compelled to surrender their personal information during transactions such as names, location, and bank accounts to facilitate payment, their privacy is put at risk, and such information can fall into unintended individuals' hands (Shi et al, 2020). Conversely, with almost all transactions taking place online, there is always the threat of cyberattacks.…”
Section: Research Themesmentioning
confidence: 99%
“…With this huge potential of opportunities for SMEs in CBEC, it is reasonable to understand the drivers, motivators, and even mitigating factors of CBEC adoption [3]. In the past, several studies on technological adoption have been conducted by scholars (e.g., [3,[10][11][12][13][14], etc. ); however, limited studies have considered the moderating role of potential variables that may mitigate the relationship of CBEC adoption [4,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%